Wheat Cost-Return Budget in Southeast Kansas - Fausett, Marvin R. (My University, 1996)
This publication outlines the expected costs and returns for wheat in southeast Kansas.
MF992_1996_10
Keywords: MF992; Economics; Crops; MF